Analisis Kadar Vanilin Dalam Buah Panili (Vanilla planifolia Andrews) Olahan Dengan Teknik Emulsi Membran Cair, Spektrofotometri dan Kromatografi Cair Kinerja Tinggi - Siti Sujalmi; Supriyanto Supriyanto; Astin Astin (Institut Teknologi Bandung, 1999)
Vanillin contents in cured vanilla, which have been stored for two years had been analyzed by liquid membrane, UV-VIS spectrophotometry, and HPLC. The analysis result by spectrophotometry UV-VIS is higher than that of HPLC. Analysis with liquid membrane emulsion extraction gave higher results than without treatment.